Haemoglobin for Fall Risk Screening in Gynaecological and Obstetric Wards: Retrospective Survey and Delphi Validation - Bijun Mao; Yan Chen; Chunsheng Wang; Yihan Ma; Huifeng Gu; Ya Shen; Luping Liu; Peihong Zhou; Huiping Jiang (Nursing Open)
ABSTRACT Aims The objective of this study is to ascertain the suitability of haemoglobin as a screening factor for falls among obstetrics and gynaecology inpatients and to formulate a stratified scheme for assessing fall risk based on haemoglobin. Design A retrospective analysis and Delphi surveys were employed for this investigation. Methods Initially, a retrospective survey analysed falls among obstetrics and gynaecology inpatients in two hospitals from January 1, 2020, to July 10, 2022. Descriptive statistics, receiver operating characteristic (ROC) curve analysis, Youden index, sensitivity and specificity were utilised for data examination. The conclusions drawn were subsequently validated by Delphi surveys, featuring 21 experts participating in five rounds of consultation. The Kappa value and the coefficient of variation (CV) were employed to assess expert advice. Results The area under the Receiver Operating Characteristic curve (AUC) of haemoglobin was 0.762 ± 0.030, 95% CI (0.703, 0.821). The highest Youden index was 0.425, with sensitivity at 0.705 and specificity at 0.720 when haemoglobin was 107.5 g/L. Two consensuses were reached by experts: anaemia was important in causing falls in obstetrics and gynaecology wards, and haemoglobin should be employed as a screening factor for falls. The stratification of anaemia was developed as follows: ≥ 110; 90–109; 60–89; and < 60 g/L. Approval for the final results was unanimous among all experts. The Kappa value (K*) was 1, and the CV of expert advice ranged from 0.092 to 0.219. Conclusions Haemoglobin could potentially be used as a predictor of fall risk in Gynaecological and Obstetric Wards. The recommended stratified scheme for anaemia in fall risk assessment is as follows: ≥ 110; 90–109; 60–89; and < 60 g/L. Implications for the Profession and/or Patient Care What problem did the study address? The study revealed a relationship between falls and haemoglobin in obstetrics and gynaecology inpatients. It also proposed a stratification scheme for assessing fall risk based on haemoglobin levels. What were the main findings? Haemoglobin has a good performance on fall risk prediction in Gynaecological and Obstetric Wards. The stratified scheme of anaemia for fall risk assessment was suggested as follows: ≥ 110; 90–109; 60–89; and < 60 g/L. Where and on whom will the research have an impact? Nurses and inpatients in obstetrics and gynaecology wards will be affected by the results of this study, and it provided a reference for fall prevention. Reporting Method This study has adhered to relevant EQUATOR guidelines and named the reporting method. No Patient or Public Contribution.